2020
DOI: 10.18280/rcma.300103
|View full text |Cite
|
Sign up to set email alerts
|

Study of Modal Behaviour of Sandwich Structure with Various Core Materials - An Analytical Approach

Abstract: The present study comprises of different types of cored sandwich structures with different core geometries. A combination of materials of skins and cores were considered to investigate the free vibrational or modal behaviour on the core materials and geometries for the structure for illuminating the vibrational aspects for failures. Subsequently, the deformation for sandwich structures with various core geometries and materials was also studied. The objective of the article is to provide an essence of vibratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…3. Analyzing the impact of temperature variation ΔT on dimensionless frequencies λ (1,1) based on four foam void ratios and three foam types. Fig.…”
Section: Analysis Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3. Analyzing the impact of temperature variation ΔT on dimensionless frequencies λ (1,1) based on four foam void ratios and three foam types. Fig.…”
Section: Analysis Resultsmentioning
confidence: 99%
“…Sandwich structures are essential in various engineering fields due to their unique properties and versatility. These structures are composed of layers bonded together to create a composite material with enhanced strength, stability, and other desirable characteristics [1]. Composite sandwich structures find wide applications in aerospace, marine, automotive, civil engineering, and transportation industries due to their high stiffness, good insulation, corrosion resistance, and energy absorption capabilities [2].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many efforts have been made to develop new designs, such as composite tubes that combine thin-walled metal tubes with other parts, which show many favorable properties [1]. The investigated components include lattice [2][3][4][5], foam [6][7][8][9], honeycomb [10][11][12][13], fold [14], ortho-grid [15,16], circumferential [17], and longitudinal corrugated [18,19] cores. It was demonstrated that the dual-bearing capacity of tube and foam improve the overall stability and mechanical performance of the combined structure [20].…”
Section: Introductionmentioning
confidence: 99%
“…22–24 The dynamic analysis of transmission tower structure could be done through the identification of vibration modes of natural frequency of the tower structures by modal testing and FE simulation. 2528…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] The dynamic analysis of transmission tower structure could be done through the identification of vibration modes of natural frequency of the tower structures by modal testing and FE simulation. [25][26][27][28] Bhowmik et al 17,18 studied about the dynamic characteristics of Carbon Polymer Nylon 66 (CPN 66) composite made transmission tower using commercial software. The authors summarized that the first vibration period was 35% that was found more than the period determined by an experienced formula.…”
Section: Introductionmentioning
confidence: 99%